Adverse Selection in the Market for Slaves: New Orleans, 1830-1860 - Greenwald, Bruce C.; Glasspiegel, Robert R. (Quarterly Journal of Economics, 1983)
This paper seeks to cast some light on the importance of adverse selection in competitive markets by examining the market for the sale of slaves in pre-Civil War New Orleans. Estimates of the degree of adverse selection in the New Orleans market are obtained by examining the relative prices of slaves from different regions of origin. These estimates indicate that slaves brought to market may on average have been of 20 percent to 40 percent lower quality than the slave population in general, and that good slaves were perhaps three times less likely to be sold than low quality ones.